Crystal Structures and Polymorphism of Nickel and Copper Coordination Polymers with Pyridine Ligands1. Issue 15 (17th November 2014) - Krysiak, Yaşar; Fink, Lothar; Bernert, Thomas; Glinnemann, Jürgen; Kapuscinski, Martin; Zhao, Haishuang; Alig, Edith; Schmidt, Martin U.
Abstract The crystal structures of a series of pyridine coordination polymers [MIICl2(C5H5N)x]n (M = Ni, Cu), prepared via thermal decomposition are reported. [NiCl2(C5H5N)4] (1) decomposes stepwise via [NiCl2(C5H5N)2]n (2), [NiCl2(C5H5N)]n (3), and [NiCl2(C5H5N)2/3]n (4), to NiCl2 with increasing temperature. The thermal decomposition of [CuCl2(C5H5N)2]n (5), progresses via two polymorphs of [CuCl2(C5H5N)]n (6a and 6b), and [CuCl2(C5H5N)2/3]n (7), to CuCl2. The compounds 3, 4, and 7 were prepared as pure phases. All crystal structures were determined by X‐ray powder diffraction. Notably, the crystal structures of the polymorphs 6a and 6b were determined from powder diffraction data of a mixture of both phases. Crystal structures of [MIICl2(C5H5N)x]n with the same x, but different metal atoms (Ni, Cu) are homeotypic, compounds 4 and 7 are isotypic. Compounds with x = 1 (3, 6a, 6b) are composed of polymeric octahedra double chains 1∞[MCl3/3Cl2/2(C5H5N)] and in case of x = 2/3 (4, 7) of triple chains. The Jahn‐Teller distortion in the copper compounds was observable with the pair distribution function (PDF) analysis.